Luteinizing hormone profiles during ovarian stimulation in assisted reproductive treatment - Verschuere, Hannah; Laenen, Annouschka; Debrock, Sophie; Tomassetti, Carla; Lie Fong, Sharon (Frontiers in Endocrinology, 2024)
Introduction: Few data is available on the natural course of luteinizing hormone (LH) during ovarian stimulation, but it has been suggested that 'oversuppressed' LH could decrease fertility outcomes. Our aim with this study is to evaluate the changes in LH depending on the used stimulation protocol to better define LH oversuppressioin.Methods: Patients undergoing oocyte retrieval in a tertiary fertility center between 01-01-2015 and 30-09-2020 after stimulation with a short-agonist (SA) or antagonist (A) protocol were included. Data were retrospectively retrieved from 858 electronic patient records, of which 338 SA cycles and 783 A cycles. A continuous profile was set out to evaluate the pooled measurements of the mean LH in time during ovarian stimulation and linear mixed modeling was used to compare the change of LH between 4 time points: the day prior to start of gonadotrophins (T1), stimulation day 5 (T2), stimulation day 6 (T3) and on the day of ovulation oocyte maturation trigger (T4). Oversuppression of LH was defined as a decrease of LH > 50% after initiation of GnRH antagonist and LH levels < 1.2 IU/l after GnRH antagonist. A subanalysis was performed for type of gonadotrophin (recFSH vs hp-hMG).Results: In the SA protocol, an initial LH peak was followed by a slow decrease of LH until ovulation triggering. In the A protocol, LH decreased after gonadotrophin initiation with a further rapid decrease after initiation of the antagonist and remained low until ovulation trigger. LH levels dropped > 50% in 26.2% of the antagonist cycles and LH levels were < 1.2 IU/l in 45.3% of cycles after initiation of GnRH-antagonist.The course of LH in the SA protocol differs from the A protocol where low mean LH levels are seen. Oversuppression of LH, or iatrogenic LH deficiency as described in earlier studies, may be a rather pervasive phenomenon during stimulation with an antagonist protocol and warrants further investigation to elucidate the clinical relevance of low LH levels during ovarian stimulation.